1985
DOI: 10.5271/sjweh.2248
|View full text |Cite
|
Sign up to set email alerts
|

Reversible nerve lesions after accidental polychlorinated biphenyl exposure.

Abstract: (1985) 91-95. Several capacitors containing polychlorinated biphenyls (PCB) exploded in a cardboard plant. During the accident, and in the clearing work, several workers were in probable contact with PCB and/or its degradation products. Nausea, intense perspiration, and headache were acute symptoms, which cleared quickly. The 15 men with the greatest exposure were studied neurophysiologically twice, namely, two and six months after the explosion. Motor conduction velocities (MCV) of the right median, ulnar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…There also was little clinical evidence of exposure-related liver or eye diseases and of neurologic conditions. This finding agrees with the general belief that systemic disorders are unlikely in man in the absence of ~hloracne.~' Seppalainen et al 42 have recently reported similar results from an investigation of 15 men accidentally exposed to PCBs from a capacitor explosion in a Finnish cardboard plant. The highest serum PCB concentrations were measured 3 days after the explosion and were comparable in magnitude to our values; they decreased to baseline levels within 1-2 mo.…”
Section: Discussionsupporting
confidence: 86%
“…There also was little clinical evidence of exposure-related liver or eye diseases and of neurologic conditions. This finding agrees with the general belief that systemic disorders are unlikely in man in the absence of ~hloracne.~' Seppalainen et al 42 have recently reported similar results from an investigation of 15 men accidentally exposed to PCBs from a capacitor explosion in a Finnish cardboard plant. The highest serum PCB concentrations were measured 3 days after the explosion and were comparable in magnitude to our values; they decreased to baseline levels within 1-2 mo.…”
Section: Discussionsupporting
confidence: 86%
“…In these studies, the PCB exposure was very high and heating/explosion was sometimes mentioned, and thus, exposure to pyrolysis products such as PCDFs may have occurred. A sex difference for some effects on the nervous system was found in some of the studies (women seemed to be more sensitive than men) (7,19,352,356,367,370). Further, various neurological symptoms have been reported in adult victims of the Yu-Cheng and Yusho incidents and cognitive deficits in women were reported recently for one of these populations.…”
Section: Neurological Effectsmentioning
confidence: 94%
“…The 15 men with the greatest exposure were studied neurophysiologically 2 and 6 months after the explosion and the results were compared to 30 unexposed workers. A reversible, slight impairment of the peripheral nerves was noted, mainly in the distal portions of sensory nerves where the conduction velocity and the amplitude of the sensory action potentials were decreased (356).…”
Section: Neurological Effectsmentioning
confidence: 99%
“…Trabalhadores expostos a concentrações elevadas de PCBs após fogo e/ou explosão de transformadores e de capacitores apresentaram moderada elevação das enzimas hepáticas, mitocondria pleomorfa, mitocondria gigante, aumento da densidade dos grânulos mitocôndri-cos, gotículas de gordura nas células hepáticas, retículo endoplasmático ligeiramente dilatado 55 , neuropatia periférica sensorial com diminuição da velocidade de condução nervosa 14 , parestesia cutânea 57 , câncer cutâneo (um caso) 54 e alterações da função respiratória do tipo obstrutivo 32 .…”
Section: Introductionunclassified